Effect of Preoperative Rehabilitation Treatment on Functional Recovery after Unilateral Total Knee Arthroplasty by Surface Electromyography - Yingping JIANG; Yunfeng SUN; Yifan ZHOU (康复学报)
Objective:To observe the effects of preoperative rehabilitation training on strength of quadriceps femoris muscle and the days of regaining normal walking ability in patients after unilateraltotal knee arthroplasty (TKA).Methods:Fourty patients who prepared to accept the TKA were randomly divided into preoperative rehabilitation group (group A, 20 cases) and postoperative rehabilitation group (group B, 20 cases). Group A accepted quadriceps muscle strengthening and aerobic exercise for seven days before operation, two groups took standard rehabilitation training including joint of motion exercise, muscle strengthening, standing and walking training, pressure therapy and low-frequency electrical stimulation of quadriceps. The root-mean-square (RMS) of quadriceps muscle was measured at the 3rd day and 7th day after operation. The days that each group need to return to normal walking function (Holden Walking Function, Level V) were compared.Results:The RMS of rectus femoris and vastus medialis muscle in group A was better than that in group B at the 3rd day after operation (P<0.05), but no significant difference was found at the 7th day after operation (P>0.05). The RMS of vastus lateralis in two groups was not difference at the 3rd day and 7th day after operation (P>0.05). There was significant difference in the average intervention days of achieving normal walking function in group A and group B (P<0.01).Conclusion:The preoperative rehabilitation can improve the muscle inhibition phenomenon after operation, reduce the hospitalization days of patients.